2016
DOI: 10.3329/fmcj.v11i1.30869
|View full text |Cite
|
Sign up to set email alerts
|

Role of Single Dose Preoperative Ceftriaxone in the Control of Surgical Site Infection in a Tertiary Level Hospital

Abstract: Post-surgical wou  infection is a crucial factor in surgical practice. Prolong use of postoperative antibiotic is common practice in our surgical world. This causes financial burden to our patients a antibiotic resistance. But international journals a  literatures suggest using antibiotics as prophylaxis only at the time of operation a  no further postoperative antibiotic is needed in clean contaminated surgery. This comparative cross-sectional study was done at the department of surgery, Sylhet MAG Osmani Med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
1
0
Order By: Relevance
“…The study concluded no differences between the groups. 41 According to Rahman et al, 2016 a single dose of ceftriaxone given preoperatively was found to be as effective as the same, followed by an injection of ceftriaxone for two days followed by oral cefixime for five days in wound infections. 42 Our meta-analysis showed no statistically significant efficacy and safety in ceftriaxone therapy compared to the preoperative comparators.…”
Section: Discussionmentioning
confidence: 99%
“…The study concluded no differences between the groups. 41 According to Rahman et al, 2016 a single dose of ceftriaxone given preoperatively was found to be as effective as the same, followed by an injection of ceftriaxone for two days followed by oral cefixime for five days in wound infections. 42 Our meta-analysis showed no statistically significant efficacy and safety in ceftriaxone therapy compared to the preoperative comparators.…”
Section: Discussionmentioning
confidence: 99%
“…Ceftriaxone (1 gm) is sufficient as a prophylaxis of surgical site infection in clean-contaminated elective surgery. 10 Pinto-Lopes et al were also unable to find any significant difference between single dose and multiple dose antibiotic prophylaxis in the incidence of postpartum infectious morbidity, endometritis and wound infection. 11 Similar result was also found in a study by Bhatnagar et al and Frank et al in 2019 found that the overall SSI rate was 5.1% in the single dose group versus 1.4% in multiple dose group without any statistical significance.…”
Section: Comparison Of Surgical Site Infectionmentioning
confidence: 94%